2002
DOI: 10.1152/ajplung.00395.2001
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase induces its own expression in Beas2B lung epithelial cells

Abstract: The urokinase-type plasminogen activator (uPA) interacts with its receptor (uPAR) to promote local proteolysis as well as cellular proliferation and migration. These functions contribute to the pathogenesis of lung inflammation and remodeling as well as the growth and invasiveness of lung neoplasms. In this study, we sought to determine if uPA alters its own expression in lung epithelial cells. Using immunoprecipitation and Western and Northern blotting techniques, we found that uPA treatment enhanced uPA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…BEAS-2B cells, a commonly studied lung epithelial model system (29,35), express both uPAR (receptor for uPA) and LRP (␣ 2 -M receptor; see Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…BEAS-2B cells, a commonly studied lung epithelial model system (29,35), express both uPAR (receptor for uPA) and LRP (␣ 2 -M receptor; see Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…6). uPA interacts with uPAR (35) in these cells while complexes between proteinases and ␣ 2 -M normally bind to LRP (25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that induction of uPA, uPA receptor (uPAR), and PAI-1 may occur in lung ECs through a uPA-mediated feedback pathway (6)(7)(8). Given the findings that uPA, PAI-1, and TF are all elevated in lung ECs during lung injury (9), we suspected that alveolar and airway ECs that were exposed to increased levels of uPA would demonstrate a concomitant increase in TF expression.…”
mentioning
confidence: 97%